Effect of Initial Headspace O2 Level on the Growth and Volatile Metabolite Production of Leuconostoc Mesenteriodes and the Microbial and Sensorial Quality of Modified Atmosphere Packaged Par‐Fried French Fries. Issue 2 (19th January 2016) - Samapundo, Simbarashe; Mujuru, Felix Mugove; de Baenst, Ilse; Denon, Quenten; Devlieghere, Frank
Abstract: This study evaluated the effect of residual O2 level (0% to 5%) on microbial growth and volatile metabolite production on par‐fried French fries packaged in a modified atmosphere with 60% CO2 (rest N2 ) at 4 °C. The results obtained showed that the initial headspace (IH) O2 level had an effect on growth of Leuconostoc mesenteroides on French fry simulation agar, whereby growth was slightly faster under 5% O2 . In terms of quantity, ethanol, 2‐methyl‐1‐propanol, and dimethyl disulphide were the most significant volatile metabolites produced by L. mesenteroides . The production of ethanol by L. mesenteroides was highest on simulation agar packaged under low IH O2 levels (0% to 1%), indicating that the fermentative metabolism was induced under these conditions. In agreement with the results observed on the simulation medium, growth of native lactic acid bacteria was faster under an IH O2 level of 5%. In addition, ethanol, 2‐methyl‐1‐propanol, and dimethyl disulphide were also quantitatively the most important volatile metabolites. However, in contrast, greater quantities of ethanol and dimethyl disulphide were produced on par‐fried French fries packaged under 5% O2 . This was attributed to the limited growth of the native flora on the par‐fried French fries under residual O2 levels of 0% and 1%. Although some significant differences ( P < 0.05) occurred between the French fries packaged in 0%, 1%, and 5 % residual O2 during storage, all products were considered to be acceptable for consumption. The results of this study can be used to optimize the shelf‐life of packaged chill stored potato products.